The lived experience of sex-integrated sport and the construction of athlete identity within the Olympic and Paralympic equestrian disciplines. Issue 8 (20th October 2016) - de Haan, Donna; Sotiriadou, Popi; Henry, Ian
Abstract: Equestrian sport is not subjected to the dominant binary sex segregation of most sports and therefore provides a unique opportunity to review how athlete 'identity' is constructed and framed within a sex-integrated sporting experience. This research draws on an ethnographic evaluation of the Olympic and Paralympic experience of the British Equestrian Team. A total of 28 interviews were conducted with riders, performance managers and support staff with transcripts subjected to Ethnographic Content Analysis. Results show clear constructs of identity, such as 'them and us', 'horsey' and 'discipline specific', with a noted absence of gender in the way interviewees describe themselves and others within the sport. Furthermore, in their accounts of their lives, there is a lack of salience of gender with regard to their identity as sports persons. The paper considers the implications of this phenomenon for a claim that equestrian sport might be described from a participant's perspective as gender neutral.